The influence of professional pilots, pilotages services, and shipping safety on the smooth flow of ship traffic - Nasution, Syahrial; Thamrin, Muhammad; Rahardjo, Sri; Saputra, D. Purwa (Edelweiss Applied Science and Technology, 2025)
This research aims to determine the role of ship pilotage in the mandatory pilotage waters, especially in the main port of Indonesia. This study seeks to assess the effect of professional pilots, pilotage services, and shipping safety on the smooth flow of ship traffic at the main port of Indonesia, managed by the largest port operator, Pelabuhan Indonesia. The research method used is Descriptive Quantitative. The data utilized in this study are primary data, obtained from a questionnaire with a Likert scale measurement ranging from 1 to 5 (strongly disagree to strongly agree), which was completed by employees at PT Pelabuhan Indonesia and stakeholders in the port. The sample consisted of 80 employees out of a population of 200. The analysis tool used in this research is Smart PLS 4.1.0.0. The data obtained are then analyzed using quantitative descriptive analysis techniques based on the primary data collected. The data will be presented in numerical form, which will then be interpreted. 1) Professional pilots have a significant effect on the smoothness of ship traffic; 2) Pilotage services have a significant effect on the smoothness of ship traffic; and 3) Shipping safety has a significant effect on the smoothness of ship traffic. Conclusion: The results of this study indicate that pilot professionalism, pilotage services, and shipping safety significantly impact the smooth flow of ship traffic in the port. These findings are important to consider in future efforts to improve and develop navigation systems and shipping management. In this study, the resulting state of the art shows that although professional pilots, pilotage services, and shipping safety are important elements in the shipping industry, their influence on the smooth flow of vessel traffic is not as strong as expected. This research provides valuable new insights for academics and practitioners in the maritime field, especially in the context of policy and the development of a more effective shipping system. Additionally, this study identifies areas that require more attention in efforts to improve the smooth flow of vessel traffic, which can form the basis for further research in the future.